PHYTOSANITARY STRUCTURE AND EPIDEMIOLOGICAL PATTERNS OF PLANT DISEASES IN AN AGROECOSYSTEM OF THE BRAZILIAN CERRADO (Editora Impacto Científico, 2026)
Plant diseases are one of the main limiting factors of agricultural productivity in tropical regions, due to the interaction between pathogens, hosts, and environmental conditions favorable to the development of epidemics. In this context, the present study aimed to carry out a phytosanitary mapping of diseases in tropical crops cultivated at the State University of Goiás, South Campus, Ipameri University Unit, identifying the main etiological agents, the predominant symptoms, and the environmental factors associated with their occurrence. The survey was conducted through systematic zigzag walking in three areas with different land uses, characterizing itself as observational and descriptive. The identification of diseases was based on symptomatological analysis in the field and on specialized phytopathological literature. The results showed a high diversity of diseases, with a predominance of fungal pathogens, highlighting genera such as Colletotrichum, Corynespora, Pseudocercospora, and Septoria, in addition to the recurrent occurrence of parasitic algae. Functional convergence of damage was observed, mainly associated with the formation of necrotic lesions and a reduction in the active photosynthetic area, regardless of the specific causal agent. The absence of systematized phytosanitary management favored the persistence of the inoculum and increased the local epidemiological risk. It is concluded that systematic phytosanitary surveys constitute a strategic tool for phytosanitary surveillance, supporting integrated disease management and the sustainability of tropical agroecosystems.DOI: https://doi.org/10.56238/edimpacto2025.090-091